A Study on the Significance of the Design Parameters of Steel Plate Shear Walls Subjected to Monotonic Loading - Honarmand, Saeed; Homami, Peyman; Gharehbaghi, Vahidreza; Noroozinejad Farsangi, Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Steel plate shear walls (SPSWs) as a resistant system against lateral loads have a high potential for earthquake energy dissipation. Due to the uncertainties of loading, construction, and installation of SPSWs, it is vital to investigate the importance of each component and achieve higher accuracy in design and the implementation of these members.
Keywords: steel plate shear walls; SPSWs; sensitivity analysis; Monte-Carlo simulation; seismic load; monotonic loading; ściany z blachy stalowej; analiza wrażliwości; metoda Monte Carlo; obciążenia sejsmiczne; obciążenie monotoniczne